May '68 on film: The renaissance of a political past. Issue 1 (1st July 2019) - Besnard-Scott, Laurence
AbstractSimone Weil's view that 'there is more of eternity in the past than in the present' may appear unexpected from a writer who is mostly known for her revolutionary and progressive texts, for she seems to defend a regression to a lost past; at least at first reading and if one solely reads it from a historicist perspective. On closer look, her reflections on time, originally written in French in the mid-1950s, are strangely relevant to our present time and its tendency to patronize the past. The 1968 events, and how we tend to perceive them in the now, are a case in point. Exploring the legacy of this collective protest as recorded on documentary films provides us with the opportunity to rediscover a particular kind of political activism that seems to be absent today, either absorbed into a broader mainstream culture, discredited as utopian or reduced to mere anachronism. Why should these artefacts still be viewed as evidence of the real world? And how do they materialize and sustain protest memory?